The Single-Whip Method of Yunnan Garrison Taxation, Fifteenth – Seventeenth Centuries. (2nd January 2021) - Wang, Xueying
Abstract : Due to the separated governing system of the Ming, the taxation system in garrisons differed by county. However, there is also evidence that shows that garrison land became county land in the seventeenth century, which indicates the garrison system was combined with the county system. This combination can be considered as a part of the single-whip method of garrison taxation. This paper focuses on the differences between the two taxation systems in garrison and county, as well as the single-whip reforming process of garrison taxation of Yunnan garrisons. Due to the constant conflict with barbarians and frontier empires, the Yunnan garrisons were constructed intermittently during the Ming dynasty. This led to a comparatively slow but clear process in the Yunnan garrison tax combination. In Yunnan, with the establishment of a taxation system in the fifteenth century, the military grain was taxed on individual soldiers as military duty. But this system was challenged by desertion and mess registration of military and county lands in the sixteenth century. The provincial officers and garrison officers tended to combine garrison taxation to garrison land. However, it was in use until the seventeenth century, when the land measurement and new tax standard was finally carried out by a Ming government who faced this challenge. And the garrison taxation was actually a changed garrison tax base from individual to land, transforming the garrison taxation into a land tax. When the Qing took over the governance of Yunnan, they changed garrison taxation into an non-military land tax system. Original garrison farmers were changed into government farmers, and had to pay not only a land tax, but also an additional individual tax. Finally the military duty was combined with a garrison land tax, and the difference between garrison land and county land was narrowed. The single-whip trend made the combination of garrison and county possible.